The other woman [large type] - Jones, Sandie (Thorndike Press large print basic, 2018)
HE LOVES YOU: Adam adores Emily. Emily thinks Adam's perfect, the man she thought she'd never meet. BUT SHE LOVES YOU NOT: Lurking in the shadows is a rival, a woman who shares a deep bond with the man she loves. AND SHE'LL STOP AT NOTHING: Emily chose Adam, but she didn't choose his mother Pammie. There's nothing a mother wouldn't do for her son, and now Emily is about to find out just how far Pammie will go to get what she wants: Emily gone forever. --Amazon